Direct measurement of the mass difference of 163Ho and 163Dy solves the Q-value puzzle for the neutrino mass determination - Eliseev, Sergey; Enss, Christian; Gastaldo, Loredana (Physical review letters, 2015)
The atomic mass difference of 163Ho and 163Dy has been directly measured with the Penning-trap mass spectrometer SHIPTRAP applying the novel phase-imaging ion-cyclotron-resonance technique. Our measurement has solved the long-standing problem of large discrepancies in the Q value of the electron capture in 163Ho determined by different techniques. Our measured mass difference shifts the current Q value of 2555(16) eV evaluated in the Atomic Mass Evaluation 2012 [G. Audi et al., Chin. Phys. C 36, 1157 (2012)] by more than 7σ to 2833(30stat)(15sys) eV/c2. With the new mass difference it will be possible, e.g., to reach in the first phase of the ECHo experiment a statistical sensitivity to the neutrino mass below 10 eV, which will reduce its present upper limit by more than an order of magnitude.
Die Zahl "163" ist im Titel jeweils hochgestellt
Gesehen am 09.07.2020